IMPLIKASI PSAK 68 AKIBAT DAMPAK COVID-19 TERHADAP PERUSAHAAN SEKTOR PERBANKAN DI INDONESIA - Amarsya Aurelia; Ryan Ramadhan; Erris Reyhan; Ruthfina Putri (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
The global Covid-19 outbreak coincided with the release of financial accounts in 2019. Fair value was one of the consequences. The price that would be obtained to transfer an asset or liability in an orderly transaction between market players, as defined by PSAK 68, is fair value. The goal of this research is to find out which companies have a direct impact on PSAK 68 and how companies generate financial reports in line with the Covid-19 situation. This method of research employs qualitative research methods. This type of qualitative research is descriptive in nature and tends to utilize analysis. In this study, document studies are used to examine the financial statements of banking organizations in Indonesia in 2020. According to the findings of this study, PSAK 68 is used in the financial statements of 11 out of 33 banking companies. The Covid-19 pandemic's uncertainty has a significant impact on the disclosure of assessments and inputs, as well as the sensitivity of the assessment to changes in businesses while compiling financial statements.